2014
DOI: 10.1007/s11414-014-9400-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Brief Care Management Intervention for Reducing Psychiatric Hospitalization Readmissions

Abstract: This study examines a recovery-focused care management bridging strategy implemented during time of inpatient stay with the goal to increase engagement in aftercare and reduce early psychiatric readmissions. The sample included 195 individuals who received care from a large psychiatric specialty hospital. Eighty-seven individuals were assigned to receive the intervention, while 108 individuals were assigned to the control group. Individuals in the intervention group received a brief interview prior to inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…A study evaluating the transitional care service (TCS) in male patients from an acute psychiatric unit in South Africa, which involved follow‐up phone calls, home visits, reminders for follow‐up, encouragement to adhere to treatment plan and psychoeducation, did not find a significant difference in number of readmissions (Botha, Coetzee, Koen, & Niehaus, ). Brief Care Management, which integrates a predischarge interview regarding goals and barriers to treatment in addition to usual care, had demonstrated reduced readmission rates in individuals with a high risk of readmission, when compared to those who received usual care only in a psychiatric specialty hospital in the United States (Taylor et al., ). The critical time intervention (CTI) and the brief critical time intervention (BCTI) involve support from a CTI worker during a limited transition period from hospital to community living with decreasing support over time to encourage the development of long‐term support from services, family and friends.…”
Section: Introductionmentioning
confidence: 99%
“…A study evaluating the transitional care service (TCS) in male patients from an acute psychiatric unit in South Africa, which involved follow‐up phone calls, home visits, reminders for follow‐up, encouragement to adhere to treatment plan and psychoeducation, did not find a significant difference in number of readmissions (Botha, Coetzee, Koen, & Niehaus, ). Brief Care Management, which integrates a predischarge interview regarding goals and barriers to treatment in addition to usual care, had demonstrated reduced readmission rates in individuals with a high risk of readmission, when compared to those who received usual care only in a psychiatric specialty hospital in the United States (Taylor et al., ). The critical time intervention (CTI) and the brief critical time intervention (BCTI) involve support from a CTI worker during a limited transition period from hospital to community living with decreasing support over time to encourage the development of long‐term support from services, family and friends.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the reduction of readmission, the most successful interventions aim to bridge the epistemic, professional and physical boundaries between hospital and community [14,29,63], either locating community staff on the ward, or ward staff in the community, increasing continuity of care or increasing knowledge of service users and families (see also [72]). [71]).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some studies found evidence for a reduction in readmission due to the interventions [26,28,40], many failed to evidence this effect [6,33,36]. The studies that had an effect on readmission tended to focus on either education, therapeutic relationships or increased continuity of care [28,63,64]. Many of the successful interventions bridged the boundaries between ward and community by providing care from ward based professionals in the community [28,54] or having community teams leading discharge planning on the wards [40].…”
Section: Reducing Readmissionmentioning
confidence: 99%
See 2 more Smart Citations